2015
DOI: 10.1099/ijs.0.000199
|View full text |Cite
|
Sign up to set email alerts
|

Aestuariicella hydrocarbonica gen. nov., sp. nov., an aliphatic hydrocarbon-degrading bacterium isolated from a sea tidal flat

Abstract: Aestuariicella hydrocarbonica gen. nov., sp. nov., an aliphatic hydrocarbon-degrading bacterium isolated from a sea tidal flat A Gram-staining-negative, strictly aerobic bacterial strain, designated SM-6 T , was isolated from a sea tidal flat of the Dangjin bay, South Korea. Strain SM-6 T was able to degrade a broad range of aliphatic hydrocarbons. Cells were catalase-and oxidase-positive and non-motile rods. Growth of strain SM-6 T was observed at 10-37 8C (optimum, 20-25 8C), at pH 5.5-9.0 (optimum, pH 6.5-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…S4). These characteristics were similar to those of Pseudoteredinibacter isoporae SW-11 T [4], Pseudomaricurvus alkylphenolicus KU14G T [28], Maricurvus nonylphenolicus KU41E T [29] and Aestuariicella hydrocarbonica SM-6 T [30]. Strain R142 T was non-motile, while Pseudoteredinibacter isoporae SW-11 T and Pseudomaricurvus alkylphenolicus KU14G T were motile.…”
Section: Pseudomaricurvus Alkylphenolicus Ku41g T (Ab809161)supporting
confidence: 59%
See 2 more Smart Citations
“…S4). These characteristics were similar to those of Pseudoteredinibacter isoporae SW-11 T [4], Pseudomaricurvus alkylphenolicus KU14G T [28], Maricurvus nonylphenolicus KU41E T [29] and Aestuariicella hydrocarbonica SM-6 T [30]. Strain R142 T was non-motile, while Pseudoteredinibacter isoporae SW-11 T and Pseudomaricurvus alkylphenolicus KU14G T were motile.…”
Section: Pseudomaricurvus Alkylphenolicus Ku41g T (Ab809161)supporting
confidence: 59%
“…S5). It was reported that A. hydrocarbonica SM-6 T has PE and PG as major polar lipids [30]. However, M. nonylphenolicus KU41E T contained DPG as a major polar lipid [35].…”
Section: Pseudomaricurvus Alkylphenolicus Ku41g T (Ab809161)mentioning
confidence: 98%
See 1 more Smart Citation
“…We further identified Methylibium petroleiphilum 48, Oleibacter sp. 49, Acinetobacter venetianus 50 , Marinobacter bryozoorum 41, Thalassospira xiamenensis 51, and Aestuariicella hydrocarbonica (OTU0009, annotation to NCBI ‘nr’, 99% sequence similarity)52, all of which have been described to possess the potential to degrade crude oil (Supplementary Dataset S1). Considering all oil-degraders that could be assigned to the species level, about 30% of all sequences for Dendrophyllia sp., 5% for E. fistula , and only 0.2% for R. typus were on average comprised by these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nearly complete 16S rRNA gene sequence (1348 bp) of strain MEBiC06469 T was compared with that of the top 20 closely related strains. Recently, Aestuariicella hydrocarbonica SM-6 T was described and shows 95.1 % 16S rRNA gene sequence similarity (Lo et al , 2015), but was not included in this study. A phylogenetic analysis using the 16S rRNA gene sequence was conducted using mega software version 5.2 (Tamura et al , 2011).…”
mentioning
confidence: 99%